PENGARUH GOOD CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP KINERJA PERUSAHAAN DAN IMPLIKASINYA TERHADAP NILAI PERUSAHAAN - Nency I, Yashinta; Muharam, Harjum (Diponegoro Journal of Management, 2017)
Maximizing   firm   value   are   influenced   by   several  factors,   including   firm performance and corporate characteristics. This study examines the effect of good corporate governance, growth, leverage, and firm size on firm value by using firm performance as intervening variable.Firm performance is measured by using Return on Assets (ROA) and firm value is measured by using Tobins'Q. The population of this research is registered companies in CGPI ranking by IICG in 2009-2015. Sampling was conducted using purposive sampling and  there  are  31  companies  that  qualified  as  a  sample.  This  research  used  linear regression by using Ordinary Least Square method to know the influence of independent variable consist of CGPI, growth, leverage, and firm size to firm value by using firm performance as intervening variable.The result of the research shows that CGPI variable has a significant positive effect on company performance, firm growth variable has positive effect not significant to firm performance, leverage variable has negative significant effect, and firm size variable has negative and insignificant effect, and firm performance is only able to mediate the relationship between CGPI and leverage to firm value. Thus, only CGPI and leverage have an indirect effect on firm value of CGPI rating companies listed on the BEI in 2009-2015.